Reduced joint reaction and muscle forces with barefoot running. Issue 11 (8th September 2021) - Kim, Hyun Kyung; Mei, Qichang; Gu, Yaodong; Mirjalili, Ali; Fernandez, Justin
Abstract: Barefoot running has been associated with lowered joint loading, but it remains unclear whether the biomechanical benefits are evident after mid-distance running. A musculoskeletal model was adopted for estimating lower limb joint loading for barefoot ( n = 10) versus shod ( n = 10) 5 km running. The barefoot group reduced peak joint reaction force at the hip and knee, and presented muscle force reductions compared to shod controls with significant group effects and interaction effects ( p < .05). These changes were primarily group effects as time point effects were not significant. These findings should be considered when designing barefoot running shoes, running programmes, and injury prevention programmes.